A novel fibrinogenase from Agkistrodon acutus venom protects against LPS-induced endotoxemia via regulating NF-κB pathway. (3rd September 2015) - Wang, Yingwei; Qin, Zixi; Shen, Shuhao; Xiang, Nanlin; Liu, Jun; Lin, Xi; Bai, Zhiquan; Wu, Zheng
Abstract: Context : Endotoxins including lipopolysaccharide (LPS) could cause endotoxemia which often results in excessive inflammation, organ dysfunction, sepsis, disseminated intravascular coagulation (DIC) or even death. Previously, a novel fibrinogenase (FII) showed protective effects on LPS-induced DIC via activating protein C and suppressing inflammatory cytokines. Objective : To evaluate whether FII has protective effect on LPS-induced endotoxemia in mice and learn about the role of NF-κB pathway in TNF-α producing process. Methods : BALB/C mice were intraperitoneally injected (i.p.) with (a) 30 mg/kg LPS, (b) LPS + 0.3 mg/kg FII, (c) LPS + 1.0 mg/kg FII, (d) LPS + 3.0 mg/kg FII or (e) saline. Both survival rate and organ function were tested, including alanine aminotransferase (ALT), blood urine nitrogen (BUN) and tissue section, and TNF-α was examined by ELISA. RAW 264.7 macrophage was administered with (a) LPS, (b) LPS + FII, (c) FII alone or (d) saline, and TNF-α and phosphorylation (P)-NF-κB (P65) were determined by Western blot. Results : The administration of LPS led to 65% mortality rate, a rise of serum TNF-α, BUN and ALT levels, and both liver and renal tissue damage were observed. While FII treatment significantly increased the survival rate of LPS-induced endotoxemia mice model, histopathology and protein analysis results also revealed that FII remarkably protected liver and renal from LPS damage as well as decreasing TNF-α level. In vitro, FII significantly decreased LPS-induced TNF-α production and the expression of P-NF-κB (P65). Conclusions : Our findings suggested that FII had protective effect on LPS-induced endotoxemia and organ injuries by suppressing the activation of NF-κB which decreased TNF-α level.